2020
DOI: 10.3847/2041-8213/ab5db3
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observations of the Formation of Periodic Collisionless Plasma Shocks from Fast Mode Waves

Abstract: It has been long theorized, but not directly observed, that low-frequency magnetosonic plasma waves can steepen and form shocks. We show an example of small-amplitude, sinusoidal magnetosonic waves at the proton gyrofrequency upstream of the Martian bow shock. We hypothesize that these waves are produced by an ion beam instability associated with the ionization of hydrogen atoms by charge exchange with solar wind protons, solar photoionization, and/or electron impact ionization. As the waves are convected towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…At Earth, the foreshock region has been crossed multiple times by various spacecrafts, which facilitates extensive statistical studies of nonlinear waves (Tsurutani and Rodriguez, 1981;Schwartz et al, 1992;Giacalone et al, 1993;Mann et al, 1994;Stasiewicz et al, 2003;Behlke et al, 2004;Lucek et al, 2004). Similarly, nonlinear waves were recently studied in great detail at Mars, where the Maven mission provided high-resolution measurements of magnetic fields and particle properties (Fowler et al, 2018;Shan et al, 2020). In contrast to planetary missions, cometary missions previous to Rosetta were exclusively fast flybys or impacts, which only provided limited information on the properties of nonlinear waves for a fixed cometary activity level.…”
Section: Introductionmentioning
confidence: 99%
“…At Earth, the foreshock region has been crossed multiple times by various spacecrafts, which facilitates extensive statistical studies of nonlinear waves (Tsurutani and Rodriguez, 1981;Schwartz et al, 1992;Giacalone et al, 1993;Mann et al, 1994;Stasiewicz et al, 2003;Behlke et al, 2004;Lucek et al, 2004). Similarly, nonlinear waves were recently studied in great detail at Mars, where the Maven mission provided high-resolution measurements of magnetic fields and particle properties (Fowler et al, 2018;Shan et al, 2020). In contrast to planetary missions, cometary missions previous to Rosetta were exclusively fast flybys or impacts, which only provided limited information on the properties of nonlinear waves for a fixed cometary activity level.…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental physical processes of reformation in collisionless shocks are poorly understood and are far from being settled, in part due to limited in situ measurements of the processes. A few studies have shown evidence of nonstationarity and reformation at the terrestrial (Dimmock et al, 2019; Lefebvre et al, 2009; Lobzin et al, 2007; Mazelle et al, 2010; Sundberg et al, 2017), and planetary bow shocks (Shan et al, 2020; Sulaiman et al, 2015; Tiu et al, 2011). Nonstationarity can also manifest itself in the form of shock ripples formed near the shock overshoot (Johlander et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In quasiperpendicular supercritical shocks, which are emphasized in this letter, the angle between the upstream magnetic field and the local normal vector to the shock surface ( θ bn ) is greater than 45°, and they exhibit a well‐defined and clear transition that includes a foot, ramp, and overshoot (Burgess & Scholer, 2015; Leroy et al, 1982). At quasiparallel shocks ( θ bn <45°), upstream particle dynamics, trajectories, and turbulence are very different (Shan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetosonic packets termed as shocklets were observed (Omidi & Winske, 1990; Tsurutani et al., 1989). Recent observations near Mars revealed periodic formations related with the pick‐up ions (Madanian et al., 2020; Shan, Du, et al., 2020; Shan, Tsurutani, et al., 2020). While specific drivers of reformation are often unclear, this topic is an active research area now.…”
Section: Introductionmentioning
confidence: 99%